2016
DOI: 10.1155/2016/4717061
|View full text |Cite
|
Sign up to set email alerts
|

The AMBU® Aura-i™ Laryngeal Mask and LMA Supreme™: A Randomized Trial of Clinical Performance and Fibreoptic Positioning in Unparalysed, Anaesthetised Patients by Novices

Abstract: Introduction. Manikin studies' data cannot accurately be extrapolated to real-life scenarios and inherent differences in design and materials of newer products may affect their clinical performance. Methods. Hence, we compared the AMBU® Aura-i™ and LMA Supreme™ in this randomized trial involving 100 ASA 1-2 unparalysed anaesthetised patients undergoing minor gynaecological surgery. Investigators had <20 Aura-i insertions. Primary outcome was time to achieve effective ventilation and secondarily insertion param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 11 publications
8
7
0
Order By: Relevance
“…The average time (standard deviation [SD]) taken for device insertion was 17.32 (8.48) s. This was comparable to other SGDs[ 7 9 13 ] though faster insertion times have been also reported. [ 12 ] AG was inserted with moderate ( n = 11) or high resistance ( n = 1) in 12 patients which is half of what has previously reported in paediatric patients[ 7 ] or with AMBU ® Aura-i™.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The average time (standard deviation [SD]) taken for device insertion was 17.32 (8.48) s. This was comparable to other SGDs[ 7 9 13 ] though faster insertion times have been also reported. [ 12 ] AG was inserted with moderate ( n = 11) or high resistance ( n = 1) in 12 patients which is half of what has previously reported in paediatric patients[ 7 ] or with AMBU ® Aura-i™.…”
Section: Discussionsupporting
confidence: 64%
“…The main finding of this study was that the AG can be an adequate ventilating device in terms of insertion and ventilating features, with an overall 100% insertion rate with timeframes comparable to other SGDs. [ 4 9 ] However, when assessed as conduit for intubation, it underperformed with a failure rate of 9%. To the best of our knowledge, there are no studies evaluating the utility of AG as a conduit for FOB-guided intubation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That result was obtained by other authors [3739], since scopolamine is a muscarinic cholinergic receptor antagonist which causes memory impairments in rodents especially in the processes of learning acquisition and short-term memory [4042]. The fact that pretreatment with M. inermis for 8 days increased IR and decreased TL indicated the improvement in learning and memory in normal mice (without scopolamine).…”
Section: Discussionsupporting
confidence: 69%
“…In our study, the glottic view was reported as grade 1 in 80% of patients in group 1 and 92% of patients in group 2. Similarly, in a previous case study using Ambu Aura-i, the glottic view was reported as grade 1 in 88% of patients and grade 2 in 10% of patients, whereas in 2% of patients, grade 3 was observed [2]. Jagannathan et al in their study also used similar criteria for grading the glottic view [9].…”
Section: Discussionmentioning
confidence: 68%